Enhancing employee engagement : an evidence-based approach - Whittington, J. Lee (Palgrave Macmillan, 2017)
This book provides an evidence-based approach to understanding declining levels of employee engagement, offering a set of practices that individuals and organizations can adopt in order to improve productivity and organizational performance. It introduces a model outlining how the experience of meaningful work impacts engagement and other organizational attitudes and behaviors. It recognizes the antecedents and consequences of such behavior, recognizing that they must be considered as components of an organizational system rather than in isolation. It will be useful for scholars and practitioners in identifying and remedying the endemic trend of disconnected workers and their negative impact on organizational goals.
Keywords: Employee motivation.; Employees -- Attitudes.; Leadership.; Personnel management.; Economics -- Sociological aspects.; elektronické knihy; electronic books